Answer:
Step-by-step explanation:
The given equations are:
[tex]2x+3y=15[/tex] (1)
and [tex]x-3y=3[/tex] (2)
Now, simply adding equation (1) and equation (2), we get
[tex]2x+3y+x-3y=15+3[/tex]
[tex]3x=18[/tex]
[tex]x=6[/tex]
Now, substituting the value of x=6 in equation (2). we get
[tex]6-3y=3[/tex]
[tex]6-3=3y[/tex]
[tex]3=3y[/tex]
[tex]y=1[/tex]
Thus, the values of x and y are 6 and 1 respectively.
In order to solve the system of solution, beau can see that in both the given equations, coefficient of y is same and is with opposite sign, thus simply adding both the equations will eliminate y and she will get the value of x and then substituting the value of x in any of the equations, she can get the value of y. With this, she can get closer to the solution.